Persepsi Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) Terhadap Minat Penggunaan Aplikasi Akuntansi Digital Di Kota Padang - Fitrianisa, Elsya; Dwiharyadi, Anda; Afni, Zalida (Akuntansi dan Manajemen, 2023)
The continue development of digital technology has had a major impact on the business world. Especially MSMEs. The most noticeable impact is the shift in data processing from manual system to computerized system. The existence of MSMEs, has not been separated from the obstacles, one of which is related to bookkepping or making financial reports. Digital based accounting applications exist as one of the technologies that are expected to overcome the problems faced. Even though digital accounting applications are available, both free and paid, there are still business actors who don’t use these applications. Meanwhile, the use of digital applications can make it easier for business actors to make decision. Therefore, it is necessary to increase the awareness of business actors to carry out digital bookkeeping. This research was conducted to determine the perceptions of MSME business actors regarding their interest in using digital accounting applications in Padang City. The theories used in this research are TAM and UTAUT. The population in the study were MSMEs in Padang City. Sampling was carried out using the purposive sampling method. The criteria for selecting the sample used were MSMEs based on data from the Department of Cooperatives and SMEs that have and have not used digital accounting applications. The results of this research indicate that perceived usefulness, perceived ease of use, behavioral intention to use, and attitude towards using technology do not influence the use of digital accounting applications for those who have not yet use or have already used the application. Meanwhile, the actual use of technology has no effect on the use of digital accounting applications for those who have not used or have used the application.